STEMI time delays: a clinical perspective: Editorial comment on the article by Verweij et al. - de Boer, M-J. (Neth Heart J, 2015)
STEMI time delays have been introduced as a performance indicator or marker of quality of care. As they are only one part of a very complex medical process, one should be aware of concomitant issues that may be overlooked or even be more important with regard to clinical outcome of STEMI patients. In this overview we try to summarise the most important ones.